'Come up to a place like this?' The Problem with Seeking Sanctuary in the Rural in Mary Lavin's Short Stories. Issue 2 (November 2019) - Flynn, Deirdre
Abstract : Mary Lavin's stories subtly suggest that the rural idyll that De Valera dreamed of cannot materialise. The past plays heavy on the modernity promised, and through Lavin's ecocritical eye, it creeps in to each of her stories like the 'powdery green lichen' that covered the walls in the yard of Ella and Robert's home in 'A Happy Death'. Her characters are not romantic outsiders but people trying to come to terms with, and move away from, the sentimentality and cliché of Irish identity. The negotiation that the characters undergo, and the influence of this pastoral trope on their lives, is manifested in Lavin's use of ecological signposts. Her stories act as a reminder of this failed rural promise and allow Lavin to make a critical statement on the promise of post-independence Ireland, and the reality of life. The environment becomes a dominating presence on the landscape, both urban and rural and on the characters that inhabit this newly independent state. This article will investigate Lavin's engagement with the rural in her short stories.